Dietary Vitamin K Intake and HPV-Infection Status Among American Women: A Secondary Analysis From National Health and Nutrition Examination Survey Data From 2003 to 2016 - Yinhui Jiang; Yinhui Jiang; Yinhui Jiang; Shu Xu; Jinzhi Lan; Jinjuan Zhang; Jinjuan Zhang; Tengxiang Chen; Tengxiang Chen (International Journal of Public Health, 2022)
Objective: Cervical cancer is a serious potential risk to women’s health, and is closely related to persistent HPV infection. Vitamin K mainly existed in green vegetables, fruit, and dairy products. This research aims to observe the association between vitamin K and HPV-infection.Methods: 13,447 participants from the NHANES were selected. Dietary vitamin K intake was used as the objective independent variable and continuous variable, HPV-infection status was used as the outcome variable, and characteristics of selected participants were used as the covariates.Results: There was a nonlinearity between vitamin K intake and HPV-infection, and the inflection point is 3.81 of log2 vitamin K intake. In a range of 0–3.81, Each one-unit increase in log2 vitamin K intake was associated with a 43% reduction in the risk of HPV infection. When log2 vitamin K intake excess of 3.81, the risk of HPV infection did not continue to decline. The HPV-subtype was not associated with vitamin K intake.Conclusion: There is a nonlinearity between vitamin K intake and HPV-infection status. But HPV-subtype was not associated with vitamin K intake.